Exploring the Mediating Role of Digital Literacy and Moderating Role of Security Perception in Fintech Trust and Digital Payment Adoption - Khairunnisa, Fitri; Ramadhani, Ella; Wulandari, Sekar Asri Pebri; Ningtyas, Firda Alfi (Talent: Journal of Economics and Business, 2025)
Amid the rapid growth of fintech adoption that is not yet matched by adequate digital literacy and trust level. This study aims to analyze the role of digital literacy in mediating the effect of trust in fintech services on the use of digital payments, as well as exploring the moderating role of perceived security in the relationship. Quantitative methods were used by collecting data from 78 respondents through questionnaires, then analyzed using SmartPLS 3. The results showed that trust in fintech services had a significant effect on digital literacy and digital payment usage. However, digital literacy does not have a significant direct effect on digital payment usage and does not significantly mediate the relationship between trust and digital payment usage. In contrast, perceived security was shown to significantly moderate the relationship between trust, digital literacy, and digital payment usage. These findings emphasize the importance of increasing digital literacy education, strengthening trust in fintech services, and effective communication about application security to users. This study also recommends a strategy based on user segmentation, especially based on the level of digital literacy and security perceptions, so that interventions are more targeted and able to encourage wider and more sustainable adoption of digital payments.